Comparison of Morphology and Protein Profile of Acetone and PBS-Fixed Toxoplasma gondii Tachyzoites for Detection of IgG and IgM Seropositivity - VALINATA, SISCA; Cahyaningsih, Umi; Nugraha, Arifin Budiman; Kurniawati, Dyah Ayu; Desem, Muhammad Ibrahim; Fong, Sulinawati (Jurnal Sain Veteriner, 2025)
Toxoplasma gondii is an obligate intracellular protozoan that causes zoonotic diseases. The prevalence of toxoplasmosis in humans in Indonesia ranges from 9.7-70%. The parasite is difficult to detect in tissues; therefore, serological testing is the most common method for detecting antibodies against Toxoplasma. Antibodies are often used as the testing criteria for IgG and IgM antibodies. Previous research has shown that agglutination testing with acetone-fixed tachyzoites was only positive for acute infection. The aim of this study was to examine microscopic changes in acetone-fixed tachyzoites, determine their ability to detect IgG and IgM seropositivity, and detect specific proteins for IgG and IgM against toxoplasmosis. Tachyzoites were fixed with acetone (A) and PBS (P). After fixation, tachyzoites were prepared to observe the morphology and sonicated to obtain Soluble Toxoplasma Antigen (STA). STA was then subjected to SDS page and western blotting. The addition of aseton resulted in morphological and protein changes. Although changes occur, acetone-fixed tachyzoites can still react with IgG and IgM seropositivity. Protein bands that can be used as IgG seropositive markers in western blot testing are bands measuring 20, 24, 27, 73, and 110 kDa, and the combination of acetone fixation with anti-goat IgM conjugate will result in seropositive bands.